2022
DOI: 10.12659/msm.938165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Serum Inflammatory Markers in Infants Under 6 Months of Age with Non-Syndromic Moderate and Severe Hearing Loss Associated with GJB2 Gene Mutations

Abstract: Background:The GJB2 gene is reported to be the main hereditary factor responsible for non-syndromic hearing impairment in infants. Several kinds of hearing loss have been linked to elevated inflammatory markers. This study aimed to evaluate serum levels of IL-2, IL-4, IL-6, IL-10, IL-17, a-TNF, and g-IFN and the severity of hearing loss. Material/Methods:Ninety newborns were divided into 3 groups: severe hearing impairment (31 infants), moderate hearing impairment (30 infants), and normal hearing (29 infants).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…IL 10 is a multicellular source, multifunctional cytokine that regulates cell growth and differentiation and is an in ammatory and immunosuppressive factor involved in in ammatory and immune responses. Zhang through the hearing screening of 90 newborns with GJB2 gene related hearing loss, found IL 10 and GJB2 related hearing severity, 19 but Haider results showed that IL 10 was signi cantly changed in tinnitus, but not in hearing loss. 20 Our MR analysis found that increased IL 10 levels are associated with increased risk of sensorineural hearing loss, and more evidence-based data are needed.…”
Section: Discussionmentioning
confidence: 99%
“…IL 10 is a multicellular source, multifunctional cytokine that regulates cell growth and differentiation and is an in ammatory and immunosuppressive factor involved in in ammatory and immune responses. Zhang through the hearing screening of 90 newborns with GJB2 gene related hearing loss, found IL 10 and GJB2 related hearing severity, 19 but Haider results showed that IL 10 was signi cantly changed in tinnitus, but not in hearing loss. 20 Our MR analysis found that increased IL 10 levels are associated with increased risk of sensorineural hearing loss, and more evidence-based data are needed.…”
Section: Discussionmentioning
confidence: 99%